(untitled) (Proceedings of Southern Federal University. Philology, 2014)
The article discusses the borrowings, primarily English that take more permanent place in the Russian linguistic culture. Their analysis is updated in the light of the problem of linguistic ecology, involving destructive phenomena in language and designed to ensure its sustainable evolution. Borrowings are investigated in terms of their pass / fail rhetorical canon, directly related to the environment of the language. The purpose of the study is to review units of other languages through the prism of their pass / fail rhetorical canon, which should be characterized in terms of the language of the linguistic ecology. Depending on the stated purpose in the work such problems are solved as the determination of the place in the system of the borrowing language; description of rhetorical categories that constitute the canon - clarity, beauty, purity, propriety of speech; establishing the nature of communication data categories. The analysis concludes that they can not only contradict the rhetorical canon, the alleged clarity, beauty, correctness, propriety of speech, but also contribute to its formation, which complies with the linguistic ecology. Key words: adoption, ecology language borrowings, rhetorical canon, normativity, the addressee, the recipient.